Analysis of Intergranular Precipitation in Isothermally Aged Nitrogen-Containing Austenitic Stainless Steels by an Electrochemical Method and Its Relation to Cryogenic Toughness - Maribel L. Saucedo-Muñoz; Victor M. Lopez-Hirata; Hector J. Dorantes-Rosales; Erika O. Avila-Davila (Advances in Materials Science and Engineering, 2011)
The precipitation process in two N-containing austenitic stainless steels, aged at temperatures between 873 and 1173 K for times from 10 to 1000 min, was analyzed by an electrochemical method based on the anodic polarization test with an electrolyte of 1 N KOH solution. The anodic polarization curves showed the following intergranular precipitation sequence: austenite → austenite + Cr23C6→ austenite + Cr23C6 + Cr2N. Besides, the fastest precipitation kinetics was detected in the aged steel with the highest content of nitrogen and carbon due to its higher driving force for precipitation. The higher the aging temperature, the higher volume fraction of precipitates. The precipitation fraction can be associated with the current density of the dissolution peaks of each phase. The Charpy-V-Notch impact energy of the aged specimens decreased with the increase in the volume fraction of precipitates.